Amino acid intake with protein food source and incident dyslipidemia in Korean adults from the Ansan and Ansung Study and the Health Examinee Study - Chung, Sangwon; Park, Jae Ho; Joung, Hyojee; Ha, Kyungho; Shin, Sangah (Frontiers in Nutrition, 2023)
Background: Dyslipidemia is a major risk factor for cardiovascular diseases and appropriate intake of amino acids may be helpful for the management of dyslipidemia. However, evidence of an association between amino acid intake and dyslipidemia in Korean adults is limited. Objective: The purpose of this study was to investigate how the incidence of dyslipidemia in Korean adults is associated with the consumption of amino acids, essential and nonessential types, as well as the sources of these amino acids from food. Methods: Data from 35,478 study participants without dyslipidemia at baseline from the Ansan and Ansung Study and the Health Examinee Study were used for the analysis. Dyslipidemia and its components such as hypertriglyceridemia, hypercholesterolemia, hyper-low-density lipoprotein (LDL) cholesterolemia and hypo-high-density lipoprotein (HDL) cholesterolemia were the main outcome in this study. The participants were categorized into quartiles, based on the intake of amino acids and plant-/animal-based proteins. Results: On average, the follow-up period lasted for 5.7 years. The two major food groups that contributed to one-half of the intake for each type of amino acid were whole grain mixed rice and white rice. Compared to the lowest quartile group, the highest quartile groups of essential amino acid intake (men: hazard ratio [HR]=0.78; 95% confidence interval [CI], 0.63–0.97; P for trend=0.0088; women: HR=0.86; 95% CI, 0.76-0.99; P for trend=0.0201) and nonessential amino acid intake (men: HR=0.75; 95% CI, 0.60-0.94; P for trend=0.0069; women: HR=0.81; 95% CI, 0.71-0.93; P for trend=0.0024) had a decreased risk of dyslipidemia. Plant-based protein intake had a negative association and animal-based protein intake had a nonsignificant association with dyslipidemia after adjustment for energy-adjusted fat intake. Furthermore, the essential and nonessential amino acid intake showed stronger negative associations with dyslipidemia after further adjustment for energy-adjusted fat intake Conclusion: To conclude, the intake of amino acids may have a protective effect against dyslipidemia in Korean adults who are aged 40 years or older, regardless of their protein food sources.